(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
The risk associated with exposure to ionizing radiation is dependent on the characteris tics of the exposed individual. The size and the structure of the individual influence the absorbed dose distribution in the organs. Although many studies have been conducted on radiation dose from medical exposure, in Bauchi, there is not much data on the assessment of patient entrance skin dose (ESD) and the health risk from conventional radiography in daily clinical practice. In this work, we estimate the ESD for adult patients undergoing X-ray examination in F.M.C. Hospital, Azare. A total of 40 patients were included in this study. ESDs were measured using thermoluminescence dosimeter badges attached to the skin surface of the X-ray beam during chest PA. Pelvic AP, lumbosacral AP, and lumbosacral lateral examinations. Patients’ biometric variables (such as age, weight, height, sex, and thickness), X-ray tube parameters (e.g., tube current and tube voltage), exposure time, focus to skin distance, and focus to film distance were recorded. The results showed that the mean values for chest PA, pelvic AP, lumbosacral AP, and lumbosacral lateral were 0.28, 2.71, 3.72, and 7.62 mGy, respectively. The measured ESD for this study ranges from 0.18 to 16.49 mGy. These values were found to be in agreement with the guidance level set by International Atomic Energy Agency and the standard diagnostic reference level.